A predictive value of hyponatremia for poor outcome and cerebral infarction in high-grade aneurysmal subarachnoid haemorrhage patients. Issue 2 (28th July 2010) - Zheng, B; Qiu, Y; Jin, H; Wang, L; Chen, X; Shi, C; Zhao, S
Abstract : Background: The clinical significance of hyponatremia has not been investigated in high-grade aneurysmal subarachnoid haemorrhage (aSAH) patients. Thus, we assessed the predictive value of hyponatremia for poor outcome or cerebral infarction in high grade patients (the World Federation of Neurological Surgeons Scale (WFNS) grade 4 or 5) after aSAH. Methods: Patients with WFNS grade 4 or 5 after aSAH were selected into this study between January 2005 and January 2008. In the same period, patients with WFNS grade 1, 2 or 3 after aSAH (low grade) were also chosen into this study. Hyponatremia was determined with serum sodium measurements obtained within 9 days after aSAH. Prognosis of patients was estimated with Glasgow Outcome Scale at 3 months. The relationship between hyponatremia and poor outcome and association of hyponatremia and cerebral infarction were analysed, respectively. Results: A total of 124 high-grade patients were included in this study. Of those, 78 patients developed hyponatremia. Hyponatremia developed in 32.3% of cases between days 1 and 3 after aSAH, and 30.6% developed hyponatremia after 3 days post-aSAH. Multivariable analysis revealed that hyponatremia was not correlated with poor outcome in high-grade aSAH patients. Furthermore, only late-onset hyponatremia was correlated with cerebral infarction in these patients. Meanwhile, there was no significant correlation between hyponatremia and poor outcome or cerebral infarction in 259 low-grade aSAH patients. Conclusions: Hyponatremia does not predict poor outcome in all-grade aSAH patients. However, late-onset hyponatremia in high-grade aSAH patients is associated with cerebral infarction. Therefore, the appropriate management of hyponatremia could be beneficial in those patients.